2019
DOI: 10.1002/jobm.201900347
|View full text |Cite
|
Sign up to set email alerts
|

Biocontrol potential of Bacillus subtilis RH5 against sheath blight of rice caused by Rhizoctonia solani

Abstract: The sheath blight disease of rice caused by Rhizoctonia solani is widely prevalent and one of the most destructive diseases, affecting rice cultivation and loss worldwide. In the present study, a set of twenty Bacillus isolates from saline soil of Uttar Pradesh were tested for their biocontrol activity against R. solani with the aim to obtain a potential strain for the control of sheath blight disease toward ecofriendly and sustainable agriculture. The results of dual‐culture assay and scanning electron micros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
39
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(40 citation statements)
references
References 47 publications
1
39
0
Order By: Relevance
“…Past studies on the antifungal activity of Bacillus revealed that Bacillus can produce defense-related antioxidant enzymes [9], N-butyl-tetrahydro-5-oxofuran-2-carboxamide [10], lipopeptide, protein [11], and other such antifungal substances. Interestingly, the content and type of volatile organic compounds (VOCs) possessing antifungal activities released by different Bacillus species during the growth process are extremely different [12][13][14].…”
mentioning
confidence: 99%
“…Past studies on the antifungal activity of Bacillus revealed that Bacillus can produce defense-related antioxidant enzymes [9], N-butyl-tetrahydro-5-oxofuran-2-carboxamide [10], lipopeptide, protein [11], and other such antifungal substances. Interestingly, the content and type of volatile organic compounds (VOCs) possessing antifungal activities released by different Bacillus species during the growth process are extremely different [12][13][14].…”
mentioning
confidence: 99%
“…The biocontrol potential and the ability to enhance plant growth of PGPB are mostly attributed to their bioactive secondary metabolites. Proteins and metabolites released in the soil by PGPB, indeed, are implicated in root colonization, as well as in interactions with the plant immune response and the surrounding niche (Lugtenberg and Kamilova, 2009;Pieterse et al, 2014;Jamali et al, 2020). The strong antimicrobial activity of selected Bacillus strains is most likely due in part to the production of hydrolytic enzymes and siderophores observed in vitro assays and confirmed by genome analysis (Table 2 and 5).…”
Section: Genome Mining For Bioactive Gene Clustersmentioning
confidence: 88%
“…Other secretion systems and efflux pumps release proteins and secondary metabolites into the medium, respectively. The secreted proteins and metabolites play roles in root colonization, as well as in interactions with the plant immune response and the surrounding prokaryotic and eukaryotic organisms (Figure 1; Lugtenberg and Kamilova, 2009;Pieterse et al, 2014;Wu et al, 2018;Jamali et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Other secretion systems and efflux pumps release proteins and secondary metabolites into the medium, respectively. The secreted proteins and metabolites play roles in root colonization, as well as in interactions with the plant immune response and the surrounding prokaryotic and eukaryotic organisms ( Figure 1 ; Lugtenberg and Kamilova, 2009 ; Pieterse et al, 2014 ; Wu et al, 2018 ; Jamali et al, 2020 ). The goal of this minireview is to describe important bacterial secreted effectors, secondary metabolites and secretion systems which play a role in the interactions of beneficial microbes with plants and surrounding microbes, including bacteria and fungi.…”
Section: Introductionmentioning
confidence: 99%